BILATERAL OTOMYIASIS IN A CHILD WITH CHRONIC SUPPURATIVE OTITIS MEDIA - W, Suwandara; M, Sudipta; Setiawan, Eka Putra (Medicina, 2013)
Myiasis is a disease that is rarely found in humans. The most often areas are the skin, nose, trachea, mouth, eye, ear and paranasal sinuses. Auriclar myiasis also known as otomyiasis is the presence of larval infestation on the human ear. In general, otomyiasis  frequently in children, but can also be found in adult who have mental retardation or cerebral palsy. We reported a case of a boy who has otomyiasis with chronic suppurative otitis media in Sanglah Hospital, Denpasar and has done manage by  evacuation of maggots, ear toilet using NaCl 0.9% and concomitant suction, topical and oral antibiotic.
Keywords: otomyasis, chronic suppurative otitis media, maggots